Implikasi Peran Auditr Internal Dalam Tata Kelola Perusahaan - Angelina Yunita Munte,; Nicodemus Christian,; Puspita Geatri Br Perangin-angin,; Vara Tiska Luthfita D P S,; Herlina Manurung , (Jurnal Mutiara Ilmu Akuntansi, 2023)
The internal audit function continues to evolve in line with changes in the business environment. In Europe, the challenging business environment is closely related to risks and corporate governance issues. As a result, a shift in the internal audit function in addressing corporate governance issues demands greater independence from the function. Responding to the need for a more independent internal audit function, a decision regarding the appointment and dismissal of the head of the internal audit and his remuneration is required, which must be approved by the supervisor. These changes indicate that the role of internal audit in the governance management relationship has changed. This research provides an overview of these changes, the trends toward an increasing role of internal audit in corporate governance, the expected benefits of internal audit independence organizations, and the future challenges in European countries.